2022
DOI: 10.3390/jcm11010271
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Hearing Screening Benefits Children, but Global Disparities Persist

Abstract: There is substantial evidence that newborn hearing screening (NHS) reduces the negative sequelae of permanent childhood hearing loss (PCHL) if performed in programs that aim to screen all newborns in a region or nation (often referred to as Universal Newborn Hearing Screening or UNHS). The World Health Organization (WHO) has called in two resolutions for the implementation of such programs and for the collection of large-scale data. To assess the global status of NHS programs we surveyed individuals potentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 51 publications
1
31
0
Order By: Relevance
“…Neuman et al, 2021 assessed the hearing screening protocols around the world for 158 countries, representing 95 % of the world's population. 14 They showed that less than one-third of the world's newborns were enrolled in UNHS programs covering at least 85 % of all babies. 14 In the EUSCREEN project 15 the pooled coverage range for all children (high and low-risk) was 97,9 % and the median 96 % (range 79-100 %) for 26 European NHS programs plus Russia, Malawi, Rwanda, India and China.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Neuman et al, 2021 assessed the hearing screening protocols around the world for 158 countries, representing 95 % of the world's population. 14 They showed that less than one-third of the world's newborns were enrolled in UNHS programs covering at least 85 % of all babies. 14 In the EUSCREEN project 15 the pooled coverage range for all children (high and low-risk) was 97,9 % and the median 96 % (range 79-100 %) for 26 European NHS programs plus Russia, Malawi, Rwanda, India and China.…”
Section: Discussionmentioning
confidence: 99%
“…14 They showed that less than one-third of the world's newborns were enrolled in UNHS programs covering at least 85 % of all babies. 14 In the EUSCREEN project 15 the pooled coverage range for all children (high and low-risk) was 97,9 % and the median 96 % (range 79-100 %) for 26 European NHS programs plus Russia, Malawi, Rwanda, India and China. 16 Moreover 20 out of 26 programs had a coverage of 95 % or higher.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Economic analysis of newborn screening by GS is particularly complex when it overlaps with an existing screen. For countries with newborn hearing screening [ 67 ], will adding a screen by GS be economically beneficial? Because of the marginal cost of adding genes connected to hearing loss to a panel that already contains several hundred treatable disorders, the potentially small improvement in detection of infants who have or will develop hearing loss in early childhood may, nevertheless, prove worthwhile.…”
Section: Choosing Conditions In Light Of Wilson and Jungner Principlesmentioning
confidence: 99%